1973
DOI: 10.1111/j.1600-0714.1973.tb01668.x
|View full text |Cite
|
Sign up to set email alerts
|

Total body irradiation effects on the bone resorption mechanism in rats subjected to orthodontic movements

Abstract: Abstract. The effect of total body irradiation on bone resorption is studied. Resorption is induced by applying an orthodontic device. A greater increase in bone resorption is observed in animals submitted to total body irradiation plus orthodontic force application, than in those submitted to orthodontic force alone. The increase in erosive areas began before an increase in the number of osteoclasts was noted. Irradiation resulted in an increased number of osteoclasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Data obtained in this experiment clearly indicated that uranyl nitrate alters the healing of sockets afler tooth extraction by inhibition of bone formation. The use of standard histometric methods (18) repeatedly proved in alveolar bone (15,16,19,20) revealed this effect in every parameter considered.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Data obtained in this experiment clearly indicated that uranyl nitrate alters the healing of sockets afler tooth extraction by inhibition of bone formation. The use of standard histometric methods (18) repeatedly proved in alveolar bone (15,16,19,20) revealed this effect in every parameter considered.…”
Section: Discussionmentioning
confidence: 90%
“…The left jaws were embedded in paraffin, sectioned and stained with hematoxylin and eosin. The first molar mesial socket was chosen as it is one of the biggest of the three mandibular molars Histometric measurements based on standard stereological methods (15)(16)(17)(18)(19)(20) were performed using an image analysing system (KiJntron MOP AM 03) on tracings oblained from projections of the sections. Bone formation and bone resorption zones observed mi-croscopically were transferred to Ihe corresponding zones on Ihe tracings.…”
Section: Methodsmentioning
confidence: 99%
“…The accuracy of the methodology used in this experiment has been repeatedly verified botb for the procedure of tooth extraction (5,8) and for the histometrie methods (5,(8)(9)(10)(11)(12), In the first case an atraumatic surgical technique was employed (5), whieh allows tooth extraction without post-operatory complications. The histometric methods are based on standard stereologic procedures and are employed to accurately assess bone aetivity (9, 10,12,14). This methodology was employed in the study of alveolar wound healing after X-radiation affording a numerical characterization ol such process (4,15).…”
Section: Discussionmentioning
confidence: 84%
“…The present study suggests that active odontoclasts are highly susceptible to low doses of PTE resulting in an increase in the numbers of nuclei per cell. The extra nuclei could arise by mitotic division of existing nuclei but in osteociasts at least, replication of DNA does not occur (Parodi et al 1973). Alternatively they could arise by fusion of existing odontoclasts which would cause a reduction in total number of cells.…”
Section: Discussionmentioning
confidence: 99%